Low systemic vascular resistance with normal blood pressure: Do we need vasopressors? - Min Woo Kang; Shin Young Ahn; Yoonjin Kang (PLoS ONE, 2025)
Background Vasoplegia is defined by systemic vascular resistance (SVR) < 800 dynes·s/cm5, cardiac index (CI) > 2.2 L/min/m2, and hypotension, and is associated with poor outcomes. Maintaining adequate blood pressure with vasopressors is considered essential in these cases. However, some patients exhibit low SVR and high CI while maintaining normal blood pressure, and the benefits of vasopressor use in this population have not been studied. Methods This study utilized the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database and included intensive care unit (ICU) patients who met the criteria for vasoplegic status, defined as SVR < 800 dynes·s/cm5, CI > 2.2 L/min/m2, and mean arterial pressure (MAP) ≥ 60 mmHg. The primary outcome was kidney deterioration, and the secondary outcome was prolonged ICU stay (defined as > 3 days). Firth’s logistic regression was used to analyze associations. Subgroup analyses and interaction term p-values were also assessed to evaluate the modifying effects of relevant variables on the relationship between vasopressor use and the outcomes. Results Among 319 patients, 6.0% experienced kidney deterioration, and 24.1% had a prolonged ICU stay. Vasopressor use was not significantly associated with kidney deterioration (odds ratio [OR]: 2.96 [0.33–29.81], p = 0.321); however, it was significantly associated with prolonged ICU stay (OR: 4.71 [2.15–10.77], p < 0.001). Sensitivity analyses confirmed these findings across vasopressor types. Subgroup analysis showed that vasopressor use was associated with a higher risk of prolonged ICU stay in patients without congestive heart failure, without heart surgery, and without chronic kidney disease. Conclusions In patients with low SVR and normal blood pressure, vasopressor use was associated with longer ICU stays but not kidney protection.